The Effectiveness of Group Dialectical Behavior Therapy on Self-doubt, Thought Fusion, and Depression in Women with Obsessive-Compulsive Disorder - Giti Nozari Kohneh Shahri; Atefeh Mahdavi Mehr; Vahid Savabi Niri; Farzin Bagheri Sheykhangafshe; Hojjatollah Farahani (Caspian Journal of Health Research)
Background: Obsessive-Compulsive Disorder (OCD) significantly impacts women, often contributing to self-doubt, thought fusion, and depression. Although Dialectical Behavior Therapy (DBT) shows promise in addressing these issues, its effectiveness within this specific population warrants further investigation. Objectives: The present study aimed to evaluate the effectiveness of DBT in reducing self-doubt, thought fusion, and depression in women with OCD. Materials and Methods: This quasi-experimental research employed a pre-test-post-test design, incorporating a control group. The study sample comprised 51 patients referred to psychological clinics and medical centers in Ardabil City in 2024. Of these, 36 women with OCD were selected via convenience sampling and randomly assigned through a lottery method to either the experimental (n=18) or the control group (n=18). The experimental group received eight 90-minute sessions of DBT, while the control group received no intervention. Data were collected using the Obsessive-Compulsive Disorder Questionnaire, Imposter Syndrome Scale, Thought Fusion Instrument, and Beck Depression Inventory. The data were analyzed using multivariate analysis of covariance in SPSS-27. Results: The findings revealed that DBT significantly reduced self-doubt (F=43.92, η2=0.60), thought-action fusion (F=55.51, η2=0.65), thought-object fusion (F=63.39, η2=0.68), thought-event fusion (F=58.76, η2=0.67), and depression (F=46.96, η2=0.61) in women with OCD (P<0.01). Conclusion: This study underscores the efficacy of DBT in significantly mitigating self-doubt, thought fusion, and depression in women with OCD. The results highlight DBT's potential to modify maladaptive cognitive and emotional patterns, thereby fostering improved psychological well-being within this population.